PENGARUH ORIENTASI WIRAUSAHA, KEMAMPUAN MANAJEMEN DAN STRATEGI BISNIS TERHADAP PRODUKTIFITAS KERJA - Roy Wahyuningsih (STKIP Persada Khatulistiwa Sintang, 2022)
This study aims to determine the effect of entrepreneurial orientation, management skills, and business strategy on work productivity in UKM shoes and sandals in Prajurit Kulon, Mojokerto Town. The method used is quantitative research. The sampling technique was carried out randomly and proportionally by region to 160 UKM of shoes and sandals. Data collection techniques using observation, interviews, documentation, and questionnaires. This study uses three independent variables, namely entrepreneurial orientation, management ability, business strategy and one dependent variable, namely work productivity, which is then analyzed using multiple regression tests. Based on the results of the study, showed partially that entrepreneurial orientation had an effect on work productivity, management ability had an effect on work productivity, and business strategy had an effect on work productivity, as well as entrepreneurial orientation, management ability, and business strategy simultaneously had an effect on work productivity. The magnitude of the influence of entrepreneurial orientation, management ability, and business strategy on work productivity is 77.75%, while the difference is contributed by other variables outside the independent variables used in this study